2021
DOI: 10.1021/acssuschemeng.1c06318
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Schiff-Base Covalent Organic Frameworks for CO2 Capture: Structure–Performance Relationships, Stability, and Performance under Wet Conditions

Abstract: Covalent organic frameworks (COFs) have been considered promising adsorbent materials for postcombustion CO2 capture due to their high porosity, tunable functionalities, and excellent framework stability. Nevertheless, few research studies have systematically investigated the structure–performance relationships and the effect of moisture on CO2 capture performance of COFs. In this study, a series of Schiff-base COFs with different functionalities, pore sizes, and framework dimensions are prepared and evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 65 publications
1
42
0
Order By: Relevance
“…COFs are endowed with fascinating properties including superb crystallinity, this important trait can be influenced by reaction conditions comprising the feeding rate of monomers, addition of a modulator, catalysis by acids or bases, and the aging process. 22 COFs with long-range order structures, superb visible light absorbance, large surface areas, and tunable band gaps have exhibited outstanding performance in diverse applications, 23 including membranes, 24 optoelectronic devices, 25 gas separation and storage 26 sensing, 27 catalysis, 28 and biomedical applications. 29 Our quest has led us to identify COFs as a promising class of materials, which can be accessed via inherently greener and sustainable MCRs and deployed in eco-friendly environmental technologies as photocatalysts, membranes for gas, and adsorbents for heavy metals and dyes.…”
Section: Introductionmentioning
confidence: 99%
“…COFs are endowed with fascinating properties including superb crystallinity, this important trait can be influenced by reaction conditions comprising the feeding rate of monomers, addition of a modulator, catalysis by acids or bases, and the aging process. 22 COFs with long-range order structures, superb visible light absorbance, large surface areas, and tunable band gaps have exhibited outstanding performance in diverse applications, 23 including membranes, 24 optoelectronic devices, 25 gas separation and storage 26 sensing, 27 catalysis, 28 and biomedical applications. 29 Our quest has led us to identify COFs as a promising class of materials, which can be accessed via inherently greener and sustainable MCRs and deployed in eco-friendly environmental technologies as photocatalysts, membranes for gas, and adsorbents for heavy metals and dyes.…”
Section: Introductionmentioning
confidence: 99%
“…Li and coworkers 18 studied water adsorption and the impact on CO 2 capture by Grand canonical Monte Carlo (GCMC) simulations of 18 chemically stable COFs, in which COF-300 exhibits excellent resistance to high relative humidity (p/p 0 = 0.8) when used to capture CO 2 . Zhao and co-workers 19 estimated a series of Schiff-base COFs for wet flue gas separation. It is indicated that keto-COFs of NUS-2 and TpPa-1 outperform the imine-COFs; moreover, they exhibit excellent hydrothermal and chemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…However, hydrophobic pores without sufficient polarity usually show poor separation performance on CO 2 / N 2 . Zhao and co-workers 19 suggested that COFs with moderate hydrophobicity would be promising adsorbent candidates for practical postcombustion CO 2 capture. An in depth and meticulous scientific issue is that what structural units can commonly make COFs show both high CO 2 /N 2 selectivity and CO 2 uptake in humid environments.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond these criteria, one important capability of the CO 2 capture sorbents is the selectivity of carbon gas toward other gases such as H 2 O and N 2 , in particular in the flue gas streams. To date, as a consequence of their high surface area and favorable mesoporous/microporous structures, various nanoporous solid-based sorbents such as metal–organic frameworks (MOFs), zeolites, covalent–organic frameworks (COFs), , porous carbons, and porous polymers have been discovered and assessed in terms of both the carbon capture capacity and selectivity. Among those solid-based adsorbents, nanoporous carbons are undeniably favorable materials not only in CO 2 capture but also in water treatment, methane storage, and catalysis due to their outstanding textural properties, overall abundance, and low cost. Although porous carbons possess advanced textural features such as a large specific Brunauer–Emmett–Teller (BET) surface area, a large pore volume, and tunable porosity, they, however, have limited performance in CO 2 adsorption capacity and selectivity efficiency owing to the lack of CO 2 -philic functionalities. , Thus, it is a necessity to decorate the porous carbons’ surface to enhance carbon capture and separation activity.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond these criteria, one important capability of the CO 2 capture sorbents is the selectivity of carbon gas toward other gases such as H 2 O and N 2 , in particular in the flue gas streams. To date, as a consequence of their high surface area and favorable mesoporous/microporous structures, various nanoporous solid-based sorbents such as metal−organic frameworks (MOFs), 9−12 zeolites, 13 covalent−organic frameworks (COFs), 14,15 porous carbons, 16−20 and porous polymers 21−23 have been discovered and assessed in terms of both the carbon capture capacity and selectivity. Among those solid-based adsorbents, nanoporous carbons are undeniably favorable materials not only in CO 2 capture but also in water treatment, methane storage, and catalysis due to their outstanding textural properties, overall abundance, and low cost.…”
Section: Introductionmentioning
confidence: 99%